Foreign Language Exposure in Knowledge-Building Forums Using English as a Foreign Language - Marni Manegre (The Canadian Network for Innovation in Education (CNIE), 2020)
This study examines whether the students with higher levels of language and cultural awareness relating to the L2 share this knowledge with their peers in collaborative writing tasks when participating in the Knowledge Building International Project (KBIP). The study was conducted in two Spanish classrooms, where the participants were bilingual in both Catalan and Spanish.  A pre-questionnaire was used to determine the level of exposure to English language and English culture and the students were scored on their responses and then divided into three groups: low-, medium-, and high-level exposure to English. A one-way ANOVA was used to determine whether exposure to English language and culture outside of the classroom would influence pre-test scores. There is an interaction effect between language and cultural exposure and the pre-test scores (F = 5.17).  Upon the conclusion of the collaborative writing task, a one-way ANOVA was used to determine whether there was an interaction effect between language and cultural exposure and the post-test scores (F = 4.47). The student scores increased at the same rate across the groups.  This indicates that the students did not share their knowledge of the English language and culture with their peers in this online writing task.